MORAL EDUCATION AS THE FOUNDATION OF ISLAMIC VALUES AND NATIONALISM ACCORDING TO KH. HASYIM ASY'ARI - Satra, Alihan; Lidia; Solihah, Maratun; Sari, Novita; Chasanah, Uswatun (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2025)
Akhlak serves as the foundation for exploring the rich educational philosophies promoted by KH. Hasyim Asy'ari, with a focus on his insights regarding moral education and the development of character within both Islamic and national identities. Employing a comprehensive library research methodology, this study synthesizes historical narratives and theological foundations that inform Asy'ari's teachings. The necessity of integrating moral education into contemporary curricula is highlighted, establishing his principles as vital for cultivating responsible and well-rounded citizens in today’s multifaceted society. Findings indicate that Asy'ari’s emphasis on faith, ethical values, and communal responsibility is crucial not only for individual development but also for fostering social cohesion amidst modern challenges. This investigation offers significant contributions to understanding the relationship between religious values and national consciousness in the context of education. Akhlak menjadi landasan dalam mengkaji filosofi pendidikan yang kaya yang dipromosikan oleh KH. Hasyim Asy'ari, dengan fokus pada pandangannya tentang pendidikan akhlak dan pengembangan karakter dalam identitas keislaman dan kebangsaan. Dengan menggunakan metodologi penelitian pustaka yang komprehensif, studi ini menyintesis narasi historis dan landasan teologis yang mendasari ajaran Asy'ari. Pentingnya integrasi pendidikan moral ke dalam kurikulum modern ditekankan, menjadikan prinsip-prinsip beliau esensial dalam membentuk warga negara yang bertanggung jawab dan seimbang di tengah masyarakat yang kompleks saat ini. Temuan menunjukkan bahwa penekanan Asy'ari terhadap iman, nilai-nilai etika, dan tanggung jawab sosial sangat krusial, tidak hanya untuk pertumbuhan individu tetapi juga untuk memperkuat kohesi sosial di tengah tantangan kontemporer. Penelitian ini memberikan kontribusi signifikan untuk memahami hubungan antara nilai-nilai religius dan kesadaran kebangsaan dalam konteks pendidikan.